Instalasi Penjernih Air Di Desa Buluh Cina, Kecamatan Siak Hulu, Kabupaten Kampar - Putri Nawangsari, Putri Nawangsari; Martin, Awaludin; Arief, Dodi Sofyan; Akbar, Mustafa; Mintarto, Mintarto; Saputra, Doni (LPPM UMRI, 2023)
Buluh Cina Village, Siak Hulu District, Kampar Regency has problems with the availability of clean water. The water that residents use comes from dug/drilled wells that smell of sulfur. This water condition is not under the drinking water requirements standardized by the Indonesian Ministry of Health through Permen Kes No. 492/MENKES/PER/IV/2010. There needs to be a solution to overcome the problem of the availability of clean water in Buluh Cina Village. The solution is to install the water filter for clean and healthy water. The Mechanical Engineering Lecturer Team at the University of Riau facilitated the water filter, which would be installed in Buluh Cina Village with a storage tank capacity of ±10,000 liters. Water-filtered results are not smelled of sulfur and are by the drinking water quality standards following Permen Kes No. 492/MENKES/PER/IV/2010.